Sagu dan Uma: Simbol Ketahanan Pangan Masyarakat Mentawai - Ramadhan, Muhammad Zaki; Delfi, Maskota; Ginting, Jonson Handrian (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
Food is a problem in human survival. This research discusses the food security of the Mentawai people who use sago as a staple food. This research uses a qualitative method with an ethnographic approach where researchers and informants live together for a certain period of time to get a good report so that the data collected truly represents the problems being faced. Sago as the staple food of the Mentawai people determines social practices in that community. The representation of the use of sago is reflected in daily activities in the Mentawai people's traditional house, known as uma.